Remembering rape: The temporal construction of sexual violence in autobiographical narratives from 1990s Finland - Frisk Matleena; Taavetti Riikka (United States, 2025)
This article examines how historical contexts affect the recollection of experiences of rape. We reanalyze sexual autobiographies that were gathered in Finland in 1992 in a sex research project called FINSEX. To illustrate how the time of the rape as well as the time it is recalled shape the possibilities of narrating a life story, we present a close reading of four autobiographies that we place in the context of the collection as a whole, and compare our analysis of the autobiographies to their interpretation in the FINSEX study. The narrative elements of the autobiographies reflect the violent experiences in complex and layered ways. For the authors of these autobiographies, temporal changes in cultural and social understandings of sexual violence enable the reinterpreting of life events and the naming of previously unnamed experiences.